Narrativa autobiográfica escrita na velhice: discurso, memória e identidade - Chediak, Sorhaya (2023)
This investigation is part of the research line Text and discourse in oral and written modalities and its theoretically supported by the Critical Discourse Analysis, based on the threedimensional conception of Fairclough (2016), which is characterized by three aspects: social practices, practical speeches and the text. The investigated object was an autobiographical narrative written in old age, in view to perceive how discursive practices interconnect with memory and individual and collective identity, as well as how social representations explain the constitution of these elements and how they reveal themselves by means of oral or written language. Based on this understanding, the research's guiding question was outlined as follows: How is the discourse of the autobiographical narrative constructed? Such questioning unfolds in others: a) How do digressions, continuities and ruptures of memory occur in the narrative discourse? b) How is identity revealed in the construction of autobiographical writing? and c) How is ethos constituted in the narrative? In searching answers to these questions, the objectives were established: general - to analyze the discourse in an autobiographical narrative, considering the constitution of memory and the temporal construction of identity; specific - a) investigate how the discourse of an autobiographical narrative is constructed; b) describe and analyze the narrative continuities and ruptures of memory in discourse; c) identify, in the speech, narrative elements of identity construction; and d) verify how ethos is constructed in the narrative, based on discourse analysis, highlighting memory and identity. To fulfill this intention, it was adopted a qualitative approach, based on the descriptive, documentary and interpretative method, which explores the discursive constitution, as well as the marks of memory and identity present in the writing. The results demonstrate that the autobiographical narrative is a form of self-representation that enables the understanding of social and cultural processes and, therefore, it has historical and sociological importance. Through such narrative, it is possible to understand memory, identity, construction of meanings, social representations and tmanifestations of ideological conceptions, as well as the subjectivity built in the relationship with the other